Soil CO2 emissions in cropland with fodder maize (Zea mays L.) with and without riparian buffer strips of differing vegetation - J. C. Dlamini; L. M. Cardenas; E. H. Tesfamariam; R. M. Dunn; J. Evans; J. M. B. Hawkins; M. S. A. Blackwell; A. L. Collins (Agroforestry Systems, 2022)
Vegetated land areas play a significant role in determining the fate of carbon (C) in the global C cycle. Riparian buffer vegetation is primarily implemented for water quality purposes as they attenuate pollutants from immediately adjacent croplands before reaching freashwater systems. However, their prevailing conditions may sometimes promote the production and subsequent emissions of soil carbon dioxide (CO 2 ). Despite this, the understanding of soil CO 2 emissions from riparian buffer vegetation and a direct comparison with adjacent croplands they serve remain elusive. In order to quantify the extent of CO 2 emissions in such an agro system, we measured CO 2 emissions simultaneously with soil and environmental variables for six months in a replicated plot-scale facility comprising of maize cropping served by three vegetated riparian buffers, namely: (i) a novel grass riparian buffer; (ii) a willow riparian buffer, and; (iii) a woodland riparian buffer. These buffered treatments were compared with a no-buffer control. The woodland (322.9 ± 3.1 kg ha − 1 ) and grass (285 ± 2.7 kg ha − 1 ) riparian buffer treatments (not significant to each other) generated significantly ( p = ) the largest CO 2 compared to the remainder of the treatments. Our results suggest that during maize production in general, the woodland and grass riparian buffers serving a maize crop pose a CO 2 threat. The results of the current study point to the need to consider the benefits for gaseous emissions of mitigation measures conventionally implemented for improving the sustainability of water resources.